One-Pot Quinazolin-4-yl-thiourea Synthesis via N-(2-Cyanophenyl) benzimidoyl isothiocyanate - P. Pazdera; J. Marek; M. Ã„ÂŒajan; W. Fathalla (Molecules, 2001)
1-substituted-3-(2-phenylquinazolin-4-yl) thioureas (7) were produced by an intramolecular cycloaddition reaction of 1-substitued-3-[(2-cyanophenylimino) phenylmethyl] thioureas (3). These compounds in turn were prepared by the reaction of N-(2-cyanophenyl)benzimidoyl isothiocyanate (2) with primary amines. The structures of products 7 were confirmed by FTIR, 1H-NMR, 13C-NMR, mass spectroscopy and X-ray crystallography.